THE EFFECTS OF CORN VARIETIES, LAYERS OF CORN HUSKS AND FIBER EXTRACTION METHODS ON CHEMICAL AND MECHANICAL PROPERTIES OF CORN HUSK FIBERS - Tamthong, Walapa; Kraisuwan, Suteeluk; Piromthamsiri, Kajijarus (Srinakharinwirot University Journal of Sciences and Technology, 2021)
The objective of this research was to study the effects of corn varieties, layers of corn husks, and fiber extraction methods on chemical and mechanical properties of corn husk fibers. A 3 x 2 x 6 factorial experiment was established in a randomized complete block design with three replication. The factors were three corn varieties: Insee 2, Hi-brix-3, and ATS 12, two layers of corn husks: outer and inner corn husks and six fiber extraction methods: method 1 using 2.5 g/l NaOH solution, method 2 using 5.0 g/l NaOH solution, method 3 using 2.5 g/l NaOH and 0.5% Cellulase enzyme solution, method 4 using 2.5 g/l NaOH and 1.0% Cellulase enzyme solution, method 5 using 5.0 g/l NaOH and 0.5% Cellulase enzyme solution, and method 6 using 5.0 g/l NaOH and 1.0% Cellulase enzyme solution were utilized. The results showed that corn varieties significantly affected fiber strength (p 0.01). The layers of corn husks and fiber extraction methods significantly affected moisture regain, fiber strength, and fiber elongation (p 0.01). The interaction between the corn varieties and layers of corn husks significantly affected moisture regain, fiber strength, and fiber elongation (p 0.01). The interaction between the corn varieties and fiber extraction methods, and the interaction between the layers of corn husks and fiber extraction methods significantly affected moisture regain, and fiber strength (p 0.01). Moreover the interaction between corn varieties, layers of corn husks, and fiber extraction methods significantly affected fiber strength (p 0.01).